Dynamics of Multimodal Components in English Educational Discourse: the Case of “English Grammar in Use” by Raymond Murphy - E. V. Kopshukova; N. V. Panina (Дискурс профессиональной коммуникации, 2024)
This article aims to identify the linguistic features of English-language educational discourse in terms of structural, descriptive, semantic, and cognitive-pragmatic analyses. The relevance of the study stems from the need to identify trends in the representation of language components in modern grammar textbooks within the communicative-pragmatic paradigm of educational discourse. The authors focus on the linguosynergetic potential of the English grammar textbook “English Grammar in Use” by Raymond Murphy, manifested in changes of certain discourse markers in all five editions. Employing a multimodal discourse analysis methodology, this research scrutinizes the verbal and visual disparities—encompassing graphic elements, letter capitalization, italics, font, and color—that hold pragmatic value and fulfill various roles, from engagement to information conveyance. The authors also investigate the interference of advertising and educational discourses and the small-format nature of texts in this self-study textbook, whose hypertext structure and internal navigational system serve as a surrogate for teacher guidance, thereby performing a directive function. A diachronic analysis of communicative scenarios within the textbook’s exercises reveals the dynamic utilization of interjections, underscoring their importance in creating an emotive-expressive backdrop that facilitates the acquisition of grammatical phenomena, reflective of their real-world application. Thus, in an attempt to represent the features of natural communication and to avoid the use of linguistic terms, the author of the textbook presents complex grammatical material in the most accessible form for a wide audience. Consequently, the study highlights the textbook’s increasing emphasis on the personality-bound component, complementing the traditionally dominant status-oriented approach in educational discourse.